Conversation analysis, institutions, and rituals - Alasuutari, Pertti (Frontiers in Sociology, 2023)
By relating conversation analysis (CA), in particular CA research on institutional interaction to such research traditions as sociological institutionalism, new materialism, and ritual theory, the article illustrates how CA scholarship can contribute to macrosociological theorizing. This argument is illustrated by how national parliaments are organized as institutions. The main point made in the article is that occasions of what CA calls institutional interaction should be considered as rituals. Although those occasions are scripted ceremonial performances wherein social pressure, material conditions, or avoidance of punishment make actors conform, they still play a role in constituting social order by making participants honor the rules and principles codified in an organization’s frontstage events. The article also underlines that organizational arrangements do not determine what actors can say or do, but they impose limits and conditions on people’s conduct. Finally, the paper suggests that it is through such arrangements of institutional interaction that social structure is created, maintained, and naturalized.